Elektrokardiogramma i uroven' elektrolitov krovi v monitoringe tekuscego funkcional'nogo sostojanija sportsmenov - Iordanskaya, F. A.; Cepkova, N. K.; Ipatenko, O. N.; Kleev, V. V. (Teorija i Praktika fiziceskoj Kul'tury, 2006)
The interrelations between ECG parameters and the level of the main blood electrolytes (Mg, Ca, Fe, I) at high level athletes has been studied. It is shown that when ECG is normal, electrolyte levels are also in normal range. at young athletes with myocardium repolarization abnormalities, there was observed more rapid pulse and higher indices of arterial blood pressure, Mg and Fe levels are at the lowest normal range. ECG abnormalities after veloergometry with Mg and P levels decrease have been also observed at young athletes. It is concluded that the preventive measures of cardiac dysfunction consist in the timely diagnostic of ECG abnormalities, express-diagnostic of blood electrolyte levels and nutritional support with a well-balanced mineral formula.